Analisis Perilaku Komunikasi Gamer Dengan Lingkungan Sekitar (Studi Kasus Pada Mahasiswa FISIP Gamer PUBG Mobile) - Halid, Rizky Djunaidi; Salakay, Selvianus (Department of Communication Science, University of Pattimura, 2023)
This is a ‘Mix Method’ research that aims to determine the effect of the online game, PUBG Mobile, on the communicative behaviour of students at the Faculty of Social and Political Sciences, Pattimura University. This research was conducted at the Faculty of Social and Political Sciences, Pattimura University, Ambon. The data collection of the mixing method was performed guantitatively and qualitatively. Quantitative data were collected through questionnaires and qualitative data was collected through interviews. The theories used for this research are Symbolic Interaction Theory, Computer-Mediated Communication Theory and McClellan’s Theory of Motivational Needs. The results showed that there was no effect of the X variable (PUBG Mobile Online Game) on the Y variable (Behaviour of communication), this can be seen in the results of quantitative data, namely the value of Sig.= 0,075 > 0,05 and count 1,810 < table 2,001 so that HO rejected Dan Ha accepted. The percentage of the R square value is only 5.3%. Quantitative data is also supported by qualitative data which confirms that there is no influence of online games on behaviour of communication.